ÇOCUKLUK ÇAĞINDA KISA BARSAK SENDROMU İLE İLGİLİ DENEYİMLERİMİZ - CELAYİR, Sinan and İLÇE, Zekeriya and Topuzlu TEKANT, Gonca and SARIMURAT, Nüvit and ERDOĞAN, Ergun and YEKER, Daver (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Short bowel syndrome (SBS) is a disease of neonatal period which appears mostly after massive bowel resection or congenital short bowel. SBS is generally seen after massive bowel resection because of malrotation, volvulus, gastrochisis, intestinal atresia, and necrotising enterocolitis. The clinical outcome is affected by the remained bowel length, presence of ileocecal valve, motility of intestine, bowel adaptation and tolerance of nutrition. The nutrition regimen complicates as septicemia and liver failure. Results.- 20 patients were followed-up during the 20 year period in our institution. The mortality rate was 60%. In these patients the remained bowel length was under 30 cm and ileocecal valve was not present or removed during the surgery. Conclusion.- In the early years of pediatric surgery the most common reason of death was bacterial overgrowth and septicemia. In the last years TPN related septicemia and liver failure are the main problem. However the main reason of mortality is septicemia in our clinic.